Electromechanical Model and Transient Behaviors of Power Systems - Xueting Cheng; Deqiang Gan (Energies)
A large-scale power system is often represented by a set of differential-algebraic equations, so-called electromechanical models. In this paper, it is shown that these models can have several analytical properties, which can be exploited to help the study of power system dynamics. These analytical properties, associated with the complete power system model and subsystem models, are described in detail. The implications of such analytical properties are also examined.